Peningkatan Derajad Kesehatan Ibu Hamil dengan Pemantauan Kadar Hemoglobin dan Edukasi Pada Ibu Hamil Untuk Mencegah Stunting - Setyowatiningsih, Lilik; Surati, Surati; Maulanah, Mochamad Rizal; Duri, Iin Desmiany (Fakultas Ilmu Kesehatan Universitas Borneo Tarakan, 2024)
Maternal Mortality Rate (MMR), both during pregnancy, childbirth and postpartum, is an important thing that must be considered, as an effort to increase the health status of mothers and the life expectancy of babies born. Maternal death cases describe the mother's health status, nutritional status, environmental health conditions and the level of availability of health services and health personnel for the mother. Based on 2019 Central Java Health Office data, the maternal mortality rate was 331 cases and Sukoharjo district recorded 5 cases of maternal death. This community service activity aims to improve the level of health of pregnant women by monitoring hemoglobin levels and increasing knowledge by providing education about anemia in pregnant women and the impact of stunting. This activity was carried out in 2 stages and 3 ways, namely by providing pre, material and post. The material is delivered directly and using leaflets. The number of participants in this activity was 50 people. The results show that the average knowledge of pregnant women increased after education was provided by providing materials and leaflets.